2D GeP3 and blue P: promising thermoelectric materials for room- and high-temperature applications. Issue 11 (5th May 2022) - Campagna, Lucas Prett; Veríssimo-Alves, Marcos; Rodrigues, Debora C. M.; Albuquerque Filho, Marcelo F. C.; Venezuela, Pedro; Scopel, Wanderlã L.; Amorim, Rodrigo G.
Abstract : Two dimensional GeP3 and blue P were investigated as a thermoelectric material using the Boltzmann model. Our study suggested that GeP3 is a good candidate as a room temperature thermoelectric material. Abstract : Thermoelectric materials have attracted great attention from the research community due to their capability to convert heat into electricity. Among these materials, two-dimensional (2D) systems are potential candidates for thermoelectric applications due to their unique electronic, mechanical and optical properties. In this work, we combine Density Functional Theory and Boltzmann Transport Equation (BTE) calculations to investigate the performance of 2D hexagonal Germanene (Ge), blue Phosphorene (blue P) and GeP3 as thermoelectric materials. The Seebeck (S), electric conductivity ( σ ) and thermal electronic conductivity ( κ e ) are obtained with the SIESTA and BoltzTraP codes by means of a module especially developed for this aim in combination with the Spglib library, while the lattice thermal conductivity ( κ  ) is obtained with the phono3py code. The studied materials have charge carrier concentrations close to 10 18 cm −2, and blue P displays the largest electric figure of merit ( ZT e ∼ 1.0), followed by GeP3 and Ge. Regarding the maximum ZT e for each of the investigated materials, we find that blue P has a central peak with ZT (blueP)e = 1.0 at T = 800 K, Germanene has a pronounced peak with ZT (Ge)e = 0.45 at T = 340 K and GeP3 has two such peaks, with and 0.98 at T = 300 K and T = 10 K, respectively. For all three compounds, κ  ( T ) in the range T = 200–700 K decreases monotonically with increasing T, with ratios and, indicating that the electronic contributions to ZT GeP3 establish its upper bound. Our findings suggest that GeP3 can be a promising room-temperature thermoelectric material if further tailoring of its electronic properties allow for an increase in ZT e .